REPRESENTASI MULTIKULTURALISME DALAM PRAKTIK SELEKSI KOLEKSI PERPUSTAKAAN SMA KOLESE GONZAGA JAKARTA - Kristiningsih, Theresia; Laksmi, Laksmi (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2021)
The value of multiculturalism needs to be applied in the school library to help school member to be able to foster a better tolerance. The school member at Gonzaga College High School who have a high diversity, this value is carried out through the practice of library collection selection. This study aims to identify the representation of multiculturalism in practice selecting collections Gonzaga College High School Library, Jakarta. The school library as a means of supporting teaching and learning activities in schools is also responsible for fostering the value of multiculturalism in students, instilling an attitude to respect diversity in language, ethnicity, and religion. This study uses a qualitative approach with ethnographic analysis methods. Data collection uses participant observation and interviews from December 2019 to April 2020, and document analysis. Determination of informants uses purposive sampling, with a total of 10 consisting of school administrators, library administrators, and students. The findings obtained indicate that the collection selection practice is carried out by referring to the school curriculum and subject-based from various disciplines. The selection tools used are book reviews from social media such as book review webinars, book title lists, and publisher catalogs, suggestions from subject teachers, school principals, and their representatives in the field of curriculum, vice principals of facilities and infrastructure, and lists of books borrowed by users. Decision-making in the practice of selection is carried out by deliberation between the head of the library and the principal based on the awareness of multicultural values on both parties, even though the decision is still held by the principal. Collection development is based on reflection and evaluation carried out by educator community as stated in Our Way Proceeding which is a guidebook in acting and deciding something. The conclusion shows that the representation of multiculturalism in the collection selection practice at the Gonzaga College High School Library applies egalitarian and democratic values. The suggestion that needs to be done is to increase regular communication between decision-makers and the head of the library.